WOMEN AS CONTENT CREATORS IN KAPUAS, CENTRAL KALIMANTAN: BALANCING SOCIAL AND ECONOMIC FROM FUNGSIONALISM STRUCTURAL PERSPECTIVE - Ardiansyah, Mawar; Nur'ain, Siti; Erawati, Desi (Jurnal Sosiologi Dialektika Sosial, 2025)
This study aims to analyses how women or mothers act as content creators in the digital economy, highlighting their primary motivations for this activity. The research method used was qualitative with a descriptive approach, in Kapuas Regency, Central Kalimantan. Primary data collection was obtained through interviews, observation, and documentation, with structural functionalism (Talcott Parsons) as the analytical tool. Secondary data were sourced from relevant journals, books, and reports. The results show that women as content creators reflect the concept of structural functionalism. Adaptation is evident in mothers' ability to learn new technologies to meet their families' economic needs. Goal attainment is reflected in their motivation to earn additional income and achieve self-actualization. Integration is demonstrated through active interaction on digital platforms, fostering social networks and solidarity. Latency (pattern maintenance) is reflected in their efforts to balance traditional values with the demands of modernity in content creation. Thus, mothers as content creators play a role as active economic agents and responsibilities for their families, strengthening social cohesion and supporting social balance in the digital era.